Potassium Cyanide (KCN) Content in Coral Reefs and Its Effect on The Abundance of Indicator-Fishes in The Anambas Islands - Rizki Dimas Permana; Sunarto Sunarto; Syawalludin Alisyahbana Harahap; Indah Riyantini; Yuwanda Ilham (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
The coral reef ecosystem has been continuously degraded in various parts of Indonesia, including the Anambas Islands. This research aimed to discover the content of Potassium Cyanide (KCN) accumulated on corals and the effect on indicator fishes abundance in the Anambas Islands. This research was conducted at 25 observation stations in the Anambas Islands National Marine Protected Area. The potassium cyanide (KCN) content was tested with the principle of titration and distillation. The coral samples used ranged from 10-20 g diluted in 100-200 ml distilled water. The method used to determine the abundance of indicator fish was underwater visual census or UVC, which recorded fish in every station. This research recorded 307 fish individuals from 14 species of the Chaetodontidae family. Potassium Cyanide's content on corals was high ranging from 0,009-0,032 mg/L with an average 0,0205 mg/L. We concluded that there was a negative correlation between the content of Potassium Cyanide (KCN) on corals and indicator fishes abundance, which means the higher the Potassium Cyanide content (KCN) is on corals, the lower the indicator fishes abundance will point out.